Bystander-Based Sexual Violence Prevention With College Athletes: A Pilot Randomized Trial - Exner-Cortens, Deinera (Journal of interpersonal violence, 2021)
The prevention of sexual violence on college campuses is a pressing public health issue. Given recent U.S. federal and state requirements for campus responses to sexual assault, many campuses may plan to implement brief, bystander-based programs to create a violence-free environment. This pilot study evaluates one such program for male undergraduate athletes, Wingman 101. The primary purpose of this study was to determine the feasibility and acceptability of participation in Wingman 101, as well as barriers to program implementation. Data for this project were collected from 80 undergraduate male athletes (M age = 19.99) on three contact sport teams in spring 2012. Participants were randomly assigned to program or a no-program control condition. Implementation data were collected at the end of each session from program participants and facilitators. Outcome data were collected over three waves (pretest, posttest, 2-month follow-up) and assessed bystander attitudes, beliefs, and behaviors. Analysis of implementation data indicated that the program was well received and implemented with high fidelity, with facilitator relatability emerging as a particularly important aspect of implementation. However, participants also listed numerous barriers to potential bystander intervention following the program. The presence of these barriers supports quantitative reductions in positive attitudes about intervention at posttest. Implications of findings for policy and practice on postsecondary campuses are discussed.